Relation between ABO blood groups and Rh group with hypertension among pregnant women attending antenatal clinic in Baquba- Diyala Province - Salman, Sawsan T. (Journal of the Faculty of Medicine Baghdad, 2014)
J Fac Med Baghdad 2014; Vol.56, No .2 Received Sep .2013 Accepted Dec. 2013 Background: Several reports show that hypertension is a leading cause of maternal and fetal morbidity; also ABO blood group may be blamed in susceptibility to human diseases as blood-group antigens which influence the bioavailability of E-selectin, TNF-alpha and intra cellular adhesion molecule-1 (ICAM1) factors that implicated in the pathogenesis of preeclampsia. Objective: To evaluate the possible relationship between ABO blood group and Rh with hypertension in pregnancy. Patients and method: Case- control study is conducted in Al-Batool teaching hospital for maternity and children in Baquba city. Two hundred and twenty (220) pregnant women with hypertension and 100 normal healthy pregnant women, in specific age group are enrolled . Comparison between hypertension and ABO blood group is done. Statistical analysis is done by X ² and t- test. Results: The results revel that mean age in hypertensive pregnant women is(30.0±6.8), while in healthy control pregnant women is (26.2±6.1) years in all ABO and Rh. blood groups. Mean weeks of gestations in hypertensive pregnant women and healthy control groups are (37.0±3.0), (35.8±6.1) respectively in all ABO and Rh blood groups. Blood group O is the highest percent (41%) in hypertensive pregnant women, (31%) in control group but it was statistically not significant p value (0.239), in control group higher percent found with blood group A (36%) comparing with blood group A in hypertensive group (33%) but also statistically not significant. Among both hypertensive pregnant women and healthy control pregnant women Rhesus positive (Rh +ve) percent is significantly higher in both hypertensive and control group (78%, 85%) respectively than Rhesus negative (Rh –ve) (22%) in hypertensive and (15%) in control, while no significant difference in the percentage of Rh+ve between the hypertensive(78%) and control group(85%) and Rh-ve in hypertensive(22%) and control(15%). Conclusion: This study reveals no association between ABO and Rh blood group and hypertension in pregnancy.